2018
DOI: 10.5937/ekopolj1803955v
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the financial position of enterprises in privatization in the agricultural sector in Serbia

Abstract: Privatization as a phase of the transitional process also included agriculture. The most attractive enterprises in agriculture, primarily in the food industry, were privatized in the first wave, while the process of privatization of other less attractive companies was slowed down and implemented mainly by the auction model. The remaining companies waiting for the privatization process are not attractive and there are problems that are expressed through poor financial position and relatively low potential. An e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…The first two ratio indicators are an indicator of financial stability, and the other two indicators are an indicator of the company's profitability. Companies with a healthy financial position are evaluated with 1 or 2, 3 points to indicate a good financial position; 4 points a bad financial position; and 5 points represents the risk of insolvency (Vukadinović et al, 2018). The result of the financial position was obtained based on the average values of the first and second indicators, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The first two ratio indicators are an indicator of financial stability, and the other two indicators are an indicator of the company's profitability. Companies with a healthy financial position are evaluated with 1 or 2, 3 points to indicate a good financial position; 4 points a bad financial position; and 5 points represents the risk of insolvency (Vukadinović et al, 2018). The result of the financial position was obtained based on the average values of the first and second indicators, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…By comparing the observed models, it was concluded that VIKOR method shows better results. Vukadinović et al (2018) applied Altman Z'-score model, Kralicek Quick test and the balanced growth model in order to determine the financial position of three companies from the agricultural sector. The research included companies which are in the process of privatization and concluded that all of the observed companies are not stable in the market and are at risk of bankruptcy.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The following Kralicek Quick test Quick test was created in 1990s with the purpose of examining the financial performance of companies using four indicators, including two indicators related to financial stability and two profitability indicators. Each indicator is assigned a score within the range from 1 to 5, where 1 represents the best and 5 the worst result (Vukadinović et al, 2018). The final result is obtained as the average of previously calculated average values of the indicators, expressed in points (Table 2).…”
Section: Kralicek Df Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the favorable natural conditions (soil and climate) for the production of various agricultural products, and access to experienced producers, top experts, and scientists [7], companies in the agricultural sector of the Republic of Serbia face substantial challenges that prevent them from realizing their full potential [8]. Agricultural companies in the Republic of Serbia face low sales prices and rising production costs [9]. The process of privatization has led to the fragmentation of large agricultural complexes, leaving a number of workers jobless.…”
Section: Introductionmentioning
confidence: 99%